2014
DOI: 10.1128/jvi.02209-13
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Deregulation of the LMP1/LMP2 Locus of Epstein-Barr Virus by Mutation of a Single CTCF-Cohesin Binding Site

Abstract: The chromatin regulatory factors CTCF and cohesin have been implicated in the coordinated control of multiple gene loci in Epstein-Barr virus (EBV) latency. We have found that CTCF and cohesin are highly enriched at the convergent and partially overlapping transcripts for the LMP1 and LMP2A genes, but it is not yet known how CTCF and cohesin may coordinately regulate these transcripts. We now show that genetic disruption of this CTCF binding site (EBV⌬CTCF166) leads to a deregulation of LMP1, LMP2A, and LMP2B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 61 publications
3
78
0
Order By: Relevance
“…To determine whether cordycepin affects EBV infection of AGS cells (gastric carcinoma), we performed cell-to-cell coinfection by using AGS [20] and LCL-EBV-GFP B-cell lymphocyte cells [21]. AGS cells (0.625 × 10 6 /well) were seeded in 6-well plates (Corning, Corning, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether cordycepin affects EBV infection of AGS cells (gastric carcinoma), we performed cell-to-cell coinfection by using AGS [20] and LCL-EBV-GFP B-cell lymphocyte cells [21]. AGS cells (0.625 × 10 6 /well) were seeded in 6-well plates (Corning, Corning, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, different variants of Epstein-Barr virus latency programs were found to depend on the assembly of alternate spatial configurations of the viral genome (Tempera et al 2011). The choice between these configurations is controlled by CTCF (Chen et al 2014). In the both abovementioned cases, the alternate spatial configurations of the genomic domains were attributed to different cell populations.…”
Section: Linear or Three-dimensional?mentioning
confidence: 96%
“…Chen et al reported that deletion of a CTCF binding site in the LMP1/LMP2 control region of the EBV genome increased the levels of both circular and linear viral genomes in the lymphoid cell lines, although the expression of the immediate-early protein Zta was unaltered (28). Similarly, deletion of the CTCF binding site in KSHV LCR led to increased expression of the lytic loci K14 and ORF74, suggesting that CTCF plays a role in restricting lytic gene expression (24).…”
Section: Discussionmentioning
confidence: 99%